Resveratrol-Loaded PCL-PEG/GO/HAP Biocomposite Bone Membranes: Evaluation of Mechanical Properties, Release Kinetics and Cellular Response - Arpaçay, Betül Meryem; Çiftçi, Fatih; Özarslan, Ali Can; Ünal, Mustafa; Kucak, Mine; Yelkenci, Aslıhan (Sage, 2025)
In this study, biocomposite membranes were developed by incorporating resveratrol (RSV)-loaded PCL-PEG composites, modified with graphene oxide (GO) and hydroxyapatite (HAP). The aim was to enhance hydrophilicity with GO and improve bioactivity with HAP. The release kinetics of RSV was evaluated by using Franz diffusion cells and compared with various kinetic models, including Korsmeyer-Peppas, Higuchi, and Baker, all of which showed high correlation coefficients (R²) close to 0.99. Mechanical tests was performed to determine the suitability of these membranes for tissue engineering applications. The composite membrane modified with GO and HAP exhibited tensile strength of 105.2 ± 5.8 MPa, tensile modulus of 3895 ± 159 MPa, elongation at break of 8.4 ± 0.9%, and toughness of 5.88 ± 0.46 MJ/m³. In vitro cell adhesion studies, visualized using DAPI fluorescence staining, demonstrated increased cell adhesion to the composite membranes over periods of 1, 3, 5, 7, and 14 days. These findings highlight the potential of the RSV-loaded PCL-PEG membranes, enhanced with GO and HAP, for applications in bone tissue engineering.
Keywords: Bone Tissue Engineering; Polymer-Matrix Composites; Drug Releasing; Release Kinetics; Biocomposite Membrane